Biting midges (Ceratopogonidae: Diptera) present in aquatic macrophytes from wetlands of Marchantaria Island, Iranduba, Central Amazonia, Brazil - Torreias, Sharlene R. S. (2013)
Ceratopogonidae (Diptera) are easily found in both aquatic and semi-aquatic sites under various environmental conditions, where their immature stages develop in areas of nutrient richness. Material was collected from six wetland areas in Ilha da Marchantaria, Iranduba, Amazonas, between July and October 2010 and February and June 2011 throughout the Amazon River’s cycle (receding and flooding stages), in aquatic macrophytes Eichhornia crassipes, Pistia stratiotes and Salvinia auriculata. The collections produced 431 immature individuals: 191 (44.3%) in E. crassipes, 125 (29%) in P. stratiotes and 115 (26.7%) in S. auriculata. After development in the laboratory 16 species were identified belonging to the following genera: Alluaudomyia Kieffer, Bezzia Kieffer, Dasyhelea Kieffer, Forcipomyia Meigen, Heteromyia Say, Neobezzia Wirth and Ratanaworabhan, Palpomyia Meigen, Paryphoconus Enderlein and Stilobezzia Kieffer. Aquatic macrophytes are excellent substrates for immature Ceratopogonidae, which are important because of their value to the balance of biodiversity in ceratofauna in wetlands.